Fourier Series Estimator For Estimation of Birespon Nonparametric Regression Curves - Agustini Tripena; Niken Larasati; Agus Sugandha; Putri Raffikah (International journal of technology and education research, 2024)
In the last decade the Fourier Series estimator in nonparametric regression (one response) has received a lot of attention from researchers because of its flexibility. In this case, the Derer Fourier estimator will be developed in two response nonparametric regression (Birespon). The shape of the regression curve is unknown and is assumed to be contained in a continuous function space . Random errors are mutually independent with zero mean and variance , and are also mutually independent with zero mean and variance . Errors are random and correlated with each other .